Criterios para articular espacios residuales al territorio: El caso del Pasaje Ermita de la Virgen en el cantón Baños de Agua Santa. - Muñoz Alban, Michelle Xiomara (2024)
Residual spaces are often neglected or underutilized land, they have the capacity to become pleasant and practical places that can generate a beneficial effect on the urban environment and increase the well-being of local inhabitants. The research focuses on the development of criteria to articulate residual spaces in the case of the Ermita de la Virgen Passage in the Baños de Agua Santa canton. To carry out this study, a qualitative methodology is used that integrates interviews, field diaries, photographs and spatial evaluation sheets to obtain real results from the place. These instruments allow a diagnosis of the socio-spatial functioning of the Ermita de la Virgen Passage. The results obtained show several deficiencies in the space, such as the lack of recreation spaces for artisans. The final proposal is structured around four main axes: spatial relationships, spatial characterization, urban framework and comfort levels. To address the identified difficulties, the focus is on providing defined guidelines for the design of the Ermita de la Virgen Passage. It is crucial to highlight that the research recognizes the relationship between residual spaces and how they influence people's ways of living, requiring a focus on urban psychographics and how they affect the emotional well-being, identity and behavior of its inhabitants. In summary, it establishes strategies for the planning and structuring of the Ermita de la Virgen Passage, with emphasis on the establishment of an adequate environment for artisans, tourists and the neighborhood community.